First report of the bordered straw, Heliothis peltigera, οn sunflower in Greece - Simoglou, K. B.; Anastasiades, A. I.; Baixeras, J.; Roditakis, E. (ENTOMOLOGIA HELLENICA, 2015)
In June 2015, infestations of sunflower crops by the bordered straw Heliothis peltigera (Lepidoptera: Noctuidae) were recorded in rural areas of the Regional Unit of Drama, N. Greece. Larval feeding-damage symptoms were observed on leaves and buds of sunflower plants, mostly at pre-flowering growth stages. Infestations were recorded in approximately 80% of the inspected sunflower fields, the infestation levels, however, were low (<5%) apparently resulting in no economic damage. The presence of H. peltigera has been reported in Southern and Central Europe, Canada, the Middle East and Africa, infesting several hosts. Infestations of sunflower crops have been reported in India, Pakistan and Sudan. To our knowledge, this is the first report of H. peltigera infestations on sunflower crops in Greece and possibly in Europe.